Revisiting China’s Rural Residential Land Consolidation: A Perspective of Functional Reconfiguration - Yujun Zhou; Hao Su (Land, 2025)
There are considerable debates about the impact of rural residential land consolidation (RRLC) on villagers. Rather than engaging in the ongoing debates of either/or choices again, this article intends to analyze the mechanisms by which RRLC benefits villagers in a specific time and location. Using L town as an example, this article demonstrates that the mechanisms by which RRLC works are dependent on the adaptive property rights functions of rural residential land (RRL), which emerged from the spontaneous and endogenous interactions among actors. Functional adjustment and substitution reconfigure the property rights functions to balance the interests of various actors. The supportive partnerships between actors make the reconfiguration process implementable, as well as ensuring that the pre-existing property rights functions and the desired functions of the various actors can be considered. The findings may provide a new perspective on evaluating RRLC and the reform of property rights, as well as valuable insights on improving the performance of government interventions.